Effects Of Health Education On Handwashing With Soap In Children Aged 10-12 Years - Edison Siringoringo; Nursyamsi (Comprehensive Health Care, 2017)
The behavior of washing hands using soap that is not true is still high in children, so it is necessary to increase knowledge and awareness by taking action on health education, where children are the group most vulnerable to disease as a result of unhealthy behavior. This study aims to determine the effect of health education on handwashing behavior using soap in children aged 10-12 years Bulukumba Regency. The population in this study were students aged 10-12 years, as many as 61 students. The sampling technique used is simple random sampling. This study uses a quasi-experimental design with a non-equivalent control group pre-test and post-test approach. The data collected were analyzed by the Wilcoxon test. Based on the Wilcoxon statistical test results obtained p-value 0.027 (<0.05) which indicates there is a significant value. So it can be concluded that there is an influence of health education on the behavior of washing hands using soap in children aged 10-12 years. The advice from researchers is to provide information and education about the importance of washing hands using soap, to all levels of society and for the future health education can be increased again.